Interaction Modeling of Red Ginger (Zingiber officinale Var. rubrum) in Ruminant Feed Wafer as Antihypertension Through in Silico - Luluatul Fajriyah; Erlix Rakhmad Purnama (Pandawa Institute, 2026)
The increasing demand for animal products requires the development of feed innovations that not only meet nutritional needs but also improve animal health. Red ginger (Zingiber officinale Var. rubrum) is known as a feed ingredient rich in nutrients and bioactive compounds. The content of secondary metabolites such as flavonoids, alkaloids, terpenoids, phenols, and essential oils has the potential to provide therapeutic effects against several diseases, one of which is hypertension. Hypertension is known as high blood pressure in a condition above the normal threshold (>140/90 mmHg) which can affect the performance of the circulatory system in ruminants, such as environmental stress, an unbalanced diet, and other metabolic disorders. Thus, it can cause a decrease in metabolic efficiency, organ dysfunction, and even death. This study aims to evaluate the interaction potential of red ginger (Zingiber officinale Var. rubrum) bioactive compounds against the ACE receptor through an in silico molecular docking approach using captopril as a reference ligand. The initial step involved exploring the bioactive compounds in red ginger, compound structure identification, Lipinski’s druglikeness test, docking, and visualization. The results showed that of the seven compounds in red ginger, when compared to captopril (control) as an antihypertensive bioactive compound candidate of -5.7 kcal/mol, the α -Cur cumene or L4 had the lowest binding affinity value compared to the other ligands at -6.8 kcal/mol when interacting with the ACE protein, thus having the potential to be further developed as a bioactive compound candidate antihypertensive in ruminant animal feed, thus indicating its potential as a candidate ACE inhibitory compound for further computational and experimental investigation.